2005
DOI: 10.1021/ac0504114
|View full text |Cite
|
Sign up to set email alerts
|

Removal of an Iron Matrix with Polyoxyethylene-Type Surfactant-Coated Amberlite XAD-4 for the Determination of Trace Impurities in High-Purity Iron

Abstract: Admicellar sorbents for the removal of an iron matrix were prepared for the determination of trace impurities in high-purity iron. A 1.0-g amount of Amberlite XAD-4 (macroreticular styrene-divinylbenzene copolymer) was coated with 0.14-1.3 mmol of polyoxyethylene-type surfactants, including polyoxyethylene-4-tert-octylphenoxy ethers (Triton X series) and polyoxyethylene-4-isononylphenoxy ethers (PONPEs). The surfactant-coated XAD-4 was packed into a polypropylene column (7 mm i.d. x 50 mm high). A 5.0-cm(3) vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…As described in our previous report, 12 the sorption of Fe(III) onto the PONPE-admicelles was quantitative in 6 -8 M HCl, while it became negligible in <2 M HCl. The separation of P(V) and As(V) from an Fe(III) matrix was thus carried out at pH 1.5, which was the optimal pH for the formation and sorption of the heteropoly acids.…”
Section: Separation Of P(v) and As(v) From Fe(iii) Matrixsupporting
confidence: 79%
See 2 more Smart Citations
“…As described in our previous report, 12 the sorption of Fe(III) onto the PONPE-admicelles was quantitative in 6 -8 M HCl, while it became negligible in <2 M HCl. The separation of P(V) and As(V) from an Fe(III) matrix was thus carried out at pH 1.5, which was the optimal pH for the formation and sorption of the heteropoly acids.…”
Section: Separation Of P(v) and As(v) From Fe(iii) Matrixsupporting
confidence: 79%
“…Compared with the previous study, 12 only a 1/10-amount of XAD-4 was used because the resulting admicelles were employed for trace analytes, not for the iron matrix. The adsorption mechanism of polyoxyethylene-type nonionic surfactants onto polystyrene surfaces has been discussed in the field of surface and colloid chemistry.…”
Section: Preparation Of Spe Sorbentmentioning
confidence: 99%
See 1 more Smart Citation
“…Many separation techniques, including sorption, [5][6][7][8][9][10][11][12] liquidliquid extraction, [13][14][15][16][17][18] coprecipitation, [18][19][20][21][22] electrolysis, 14,23,24) and volatilization, 25,26) have been employed to determine impurities at ultratrace levels in iron and steels. However, these techniques are often tedious and time-consuming and they sometimes require volatile, flammable, and ill-smelling organic solvents or corrosive and hazardous acids.…”
Section: Introductionmentioning
confidence: 99%
“…During the course of our study on the separation techniques for the analysis of iron metals, [10][11][12][13] we found that a polyoxyethylene-type nonionic surfactant-coated resin provided the quantitative extraction of heteropoly molybdic acids. 13) The desorption was made by decomposing them with an alkaline reagent and the obtained solution was acidified again to form heteropoly molybdic acids for the determination by high-performance liquid chromatography (HPLC).…”
Section: Introductionmentioning
confidence: 99%